Developing Mission : Photography, Filmmaking, and American Missionaries in Modern China - Ho, Joseph W., 1987- (Book collections on Project MUSE., 2021)
"A transnational cultural history of US and Chinese communities framed by missionary lenses-reconstructing the lives and afterlives of images, cameras, and visual imaginations. It illuminates the centrality of visual practices in modern American missionary experiences and representations of China, even as changing Sino-US relations radically transformed the lives of those behind and in front of the lens"--